Case Report: Pupil-Sparing Third Nerve Palsy Due to Diabetes Mellitus - Searles, Gordon E (Canadian Journal of Optometry, 1981)
The symptoms and diagnosis of diabetic oculomotor ophthalmoplegia are examined in a case study. The patient had a right ptosis with diplopia and paresis o all muscles subserved by the oculomotor nerve. Tests for diabetes were positive and patient was placed on therapy to control diabetes, with resolution of palsy three months after initiation of treatment. Diabetic ophthalmoplegia is a form of ischemic neuropathy that could be elicited from metabolic or vascular causes. Differential diagnosis is essential to rule out aneurysms and myasthenia gravis. The cardinal sign of diabetic palsy is the sparing of pupillary function. The case points out the importance of a careful case history to determine the cause of the condition.